2010
DOI: 10.1002/jmri.22268
|View full text |Cite
|
Sign up to set email alerts
|

Texture‐based classification of focal liver lesions on MRI at 3.0 Tesla: A feasibility study in cysts and hemangiomas

Abstract: Purpose: To determine the feasibility of texture analysis for the classification of liver cysts and hemangiomas, on nonenhanced, zero-fill interpolated T1-and T2-weighted MR images.Materials and Methods: Forty-five patients (26 women and 19 men; mean age, 58.1 6 16.9 years) with liver cysts or hemangiomas were enrolled in the study. After exclusion of images with artifacts, T1-weighted images of 42 patients, and T2-weighted images of 39 patients, obtained at 3.0 Tesla (T), were available for further analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 35 publications
(43 reference statements)
9
72
0
Order By: Relevance
“…Previous studies have shown that zero-fill interpolated images enhance physically distinct structures’ textural differences (29,30). However, it is routine clinical practice to use MR scanner software to interpolate images by automatic zero-filling of k-space to achieve a resolution of 256×256.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that zero-fill interpolated images enhance physically distinct structures’ textural differences (29,30). However, it is routine clinical practice to use MR scanner software to interpolate images by automatic zero-filling of k-space to achieve a resolution of 256×256.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nonimaging MALDI-TOF MS has been combined with linear discriminant analysis to achieve that goal ( 29 ). In microarray data sets even larger than MALDI images, Fisher discriminant analysis (FDA), a related discriminant analysis method, has successfully been applied for gene selection ( 30 ); it has previously been used for discrimination of magnetic resonance or positron emission tomography images (31)(32)(33). FDA does not make the assumptions of a t -test, such as normally distributed classes, and may therefore be suitable for analysis of MALDI-IMS data sets for which no normal distribution can be assumed.…”
mentioning
confidence: 99%
“…38 An earlier study of methylation-status prediction in glioblastoma yielded accuracies of up to 93.2%. 27 Other studies have shown that normal liver tissue could be differentiated from focal liver lesions with accuracies up to 88% 39 and that normal bladder wall could be differentiated from bladder cancer with an accuracy of 87.0%. 40 We found that texture features of the Post-Gad T1WI, T2WI, and ADC map were influential in the analysis.…”
Section: Discussionmentioning
confidence: 99%